PHYTOCHEMICAL PROFILING OF CAYENNE PEPPER (Capsicum frutescens L.) STEM EXTRACT - Siregar, Fatimah Khaerani; Rambe, Jariah; Sahara, Rifani; Daulay, Alya Nabila; Arsita, Alya; Syakirah, Ananda; Shinta, Adelia Pretty (Poltekkes Kemenkes Surakarta, 2025)
As an agricultural country, Indonesia has great potential in the utilization of biological resources, one of which is the cayenne pepper plant (Capsicum frutescens L.) which is commonly used as a cooking spice and also has health benefits. So far, the cayenne pepper, often discarded as waste, is assumed to hold potential as a value-added product due to its rich phytochemical compounds. This research focuses on detection of various secondary metabolite compounds in the extract of cayenne pepper stems through the phytochemical screening method. Extraction was carried out using ethanol solvent for maceration and providing rotary evaporator for purity. Pure extract was tested qualitatively using phytochemical screening method to identify the secondary metabolite compounds. The findings presented alkaloids, saponins, tannins, and indications of terpenoids, while flavonoids and steroids were not detected. These are influenced by the concentration of the compound, the suitability of the solvent, and the stability of the compound during the extraction process. The conclusion of this study showed that cayenne pepper stems have the potential as a source of natural ingredients containing bioactive compounds and can be developed in the pharmaceutical field.